Trap design and construction for high‐power multinuclear magnetic resonance experiments. Issue 4 (17th November 2016) - Rispoli, Joseph V.; Dimitrov, Ivan E.; Cheshkov, Sergey; Malloy, Craig; Wright, Steven M.; McDougall, Mary P.
Abstract: Performing multinuclear experiments requires one or more radiofrequency (RF) coils operating at both the proton and second‐nucleus frequencies; however, inductive coupling between coils must be mitigated to retain proton sensitivity and coil tuning stability. The inclusion of trap circuits simplifies placement of multinuclear RF coils while maintaining inter‐element isolation. Of the commonly investigated non‐proton nuclei, perhaps the most technically demanding is carbon‐13, particularly when applying a proton decoupling scheme to improve the resulting spectra. This work presents experimental data for trap circuits withstanding high‐power broadband proton decoupling of carbon‐13 at 7 T. The advantages and challenges of building trap circuits with various inductor and capacitor components are discussed. Multiple trap designs are evaluated on the bench and utilized on an RF coil at 7 T to detect broadband proton‐decoupled carbon‐13 spectra from a lipid phantom. A particular trap design, built from a coaxial stub inductor and high‐voltage ceramic chip capacitors, is highlighted owing to both its performance and adaptability for planar array coil elements with diverse spatial orientations.